Chemical Vapor Deposition of Ru/RuSe2 Catalyst for Electrolytic Hydrogen Evolution Reaction - Megersa, Daba Deme; Gudena, Gutema Teshome; Kim, Youngho; Yu, Hak Ki (Advanced Sustainable Systems, 2023)
A one-step synthesis of highly stable Ru/RuSe2 nanoparticles (NPs) on carbon paper is achieved using low temperature and pressure chemical vapor deposition (CVD), resulting in a heterointerface with multiple active sites for catalysis. The catalyst exhibits outstanding performance for the hydrogen evolution reaction (HER) in an alkaline solution, with low overpotentials and fast hydrogen adsorption and desorption kinetics. The Ru/RuSe2/C nanoparticle structure has the potential for large-scale production and can be used as an efficient catalyst for HER.
Keywords: Carbon paper; Chemical vapour deposition; Electrolytic hydrogen evolution; Hetero-interfaces; Highly stables; Hydrogen evolution reactions; Low-pressure chemical vapor deposition; One step synthesis; Ru/ruse2 nanoparticle; ]+ catalyst; catalysts; chemical vapor deposition; heterointerfaces; hydrogen evolution reaction; Ru/RuSe2 nanoparticles